Implementation of Error Detection and Correction in the Modbus-Rtu Serial Protocol - Urrea-Onate, E; Kern-Molina, J; Morales-Diaz, C (Elsevier B.V., 2016)
Modbus-RTU is currently one of the most widely-used industrial communications protocols. Modbus-RTU is an old protocol – it was developed in 1979 – and has certain limitations with regard to modern automation and control systems. One of the major limitations is that the protocol does not have any mechanisms for ensuring the integrity of transmitted data. To address the limitation, this paper presents a method for recovering corrupted frames due to transmission errors in Modbus-RTU serial communications while retaining complete compatibility with the protocol. The method uses forward error correction codes that add parity information in time windows during which the communications bus is in a rest state. The method complies with the protocol definitions and facilitates the extension of Modbus-RTU characteristics while maintaining compatibility with installed devices and other industrial equipment. © 2016 Elsevier B.V.
Keywords: SCADA systems; Modbus-RTU protocol; Error detection and correction; Legacy device compatibility